Comparing two approaches to remote biochemical verification of self-reported cessation in very low-income smokers. (June 2021) - Garg, Rachel; McQueen, Amy; Wolff, Jennifer; Butler, Taylor; Thompson, Tess; Caburnay, Charlene; Kreuter, Matthew W.
Highlights: Low-income smokers preferred urine tests over breath tests to confirm cessation. Rates of completing in-home urine tests were comparable to rates in prior studies. Many digital photos of urine test results were inconclusive, limiting their value. Urine tests are acceptable to low-income smokers, but need to yield clearer results. Abstract: Little is known about the acceptability and use of remote biochemical verification of self-reported cessation among low-income and racially diverse smokers. We compared responses to an in-person carbon monoxide breath test and in-home urine cotinine test among 270 adults who reported 7-day continuous abstinence at 6-month follow-up in a community-based randomized cessation trial. Half of participants (50%) reported annual household income below 10, 000, one in four (28%) had not completed high school, and 69% were Black or African American. Regardless of whether the two tests were offered separately, sequentially, or as a head-to-head choice, participants were more likely to accept an offer to take the urine test than the breath test (89% vs. 32%), and complete it (46% vs. 13%). The proportion of participants completing the urine test and returning a digital photo of the test result is comparable to several studies completed with less disadvantaged samples. Self-report was confirmed by urine test for 74% of participants with a conclusive test result, although a high percentage (39%) of test results were inconclusive. In-home urine testing appears both acceptable and feasible for many low-income smokers, but challenges with testing technology and response rates currently limit its value to increase confidence in self-reports.